THE INFLUENCE OF SOLVENTS ON THE ANTIOXIDANT ACTIVITY OF CHERRY EXTRACTS - Eremeeva N.B.; Makarova N.V. (Техника и технология пищевых производств)
Antioxidants can serve as a factor reducing the oxidative stress environment caused by free radicals depleting cellular system of the body. The article considers the effect of the extractant used on the extract properties. The selection of the optimal solvent (50% aqueous ethanol, 98% ethyl alcohol, water, n-hexane, benzene, ethyl acetate, chloroform) for mixture cherries as raw material is described, it being widespread in the Samara region for producing an extract having the most active antioxidants. For the study the extracts were obtained at 37 deg. C for 2 hours. In this paper, various methods for determining the antioxidant activity level are used: the content of total amount of phenolic compounds, content of gallic acid, catechin, the content of flavonoids, anthocyanins, cyanidin-3-glycoside, antiradical capacity using free radical DPPH (2,2-diphenyl-1-pikrilgidrazila), the restoring force by the method of FRAP (ferric reducing antioxidant power), antioxidant activity in the linoleic acid. A significant number of methods to assess the antioxidant activity of the compounds are classified quantitatively according to the method of recording the parameters on the basis of which the antioxidant activity is determined. It is shown that the use of ethanol, mixtures of water and alcohol-water extracts results in good antioxidant performance. In contrast, extracts prepared from n -hexane, benzene, ethyl acetate and chloroform, have low antioxidant activity.